Moringa Leaf Extract on Changes in CD36 mRNA Gene Expression in the Brain of Rats Exposed to Ethylene Glycol - Gilang Wirayudha; Zahratul Idami (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to analyze the effect of Moringa oleifera administration on CD36 mRNA expression in rat tissues exposed to ethylene glycol. The method used was an experimental design with gene expression analysis performed using RT-PCR and GAPDH as an internal control gene. The results showed that CD36 mRNA expression increased in the ethylene glycol-exposed group compared to the normal group. In the treatment groups, different doses of Moringa oleifera produced varied expression responses, where a certain dose reduced gene expression toward normal conditions, while a higher dose increased the expression again. The expression of GAPDH remained relatively stable across all groups, confirming its suitability as a reference gene. In conclusion, Moringa oleifera administration affects CD36 mRNA expression in a dose-dependent manner and has the potential to attenuate the toxic effects of ethylene glycol at specific doses. Keywords: Ethylene Glycol, Moringa Leaf, CD36 mRNA Expression